2007
DOI: 10.1098/rstb.2007.2143
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the seasons: the internal calendars of vertebrates

Abstract: Animals have evolved many season-specific behavioural and physiological adaptations that allow them to both cope with and exploit the cyclic annual environment. Two classes of endogenous annual timekeeping mechanisms enable animals to track, anticipate and prepare for the seasons: a timer that measures an interval of several months and a clock that oscillates with a period of approximately a year. Here, we discuss the basic properties and biological substrates of these timekeeping mechanisms, as well as their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
152
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(159 citation statements)
references
References 258 publications
(302 reference statements)
1
152
0
5
Order By: Relevance
“…This requirement for short days has been termed the breaking of refractoriness, but could also be seen as an advance of the underlying circannual system which in some species is obligatory [15,43,47]. Hence, it is not excluded that photorefractoriness, in birds and in mammals, could depend on a similar circannual timing mechanism [2,22,24].…”
Section: (C) Photoperiodic Response Mechanisms Of Circannual Clocksmentioning
confidence: 99%
See 2 more Smart Citations
“…This requirement for short days has been termed the breaking of refractoriness, but could also be seen as an advance of the underlying circannual system which in some species is obligatory [15,43,47]. Hence, it is not excluded that photorefractoriness, in birds and in mammals, could depend on a similar circannual timing mechanism [2,22,24].…”
Section: (C) Photoperiodic Response Mechanisms Of Circannual Clocksmentioning
confidence: 99%
“…Perhaps we have retained a circannual timer that can be synchronized by photoperiod or metabolic status [15,111,112]. Alternatively, as our ancestors moved from Africa to the higher latitudes and encountered progressively greater variation in food availability and temperature, they could have evolved a strong photoperiodic response [7,24].…”
Section: (B) Urbanizationmentioning
confidence: 99%
See 1 more Smart Citation
“…There are complex interactions between the reproductive system and the environment that involve state variables other than the state of reproductive system (see Hahn & MacDougall-Shackleton 2008;Paul et al 2008;Wikelski et al 2008). Many studies of behaviour over the annual cycle have shown that cues such as short days trigger a particular phase of the life cycle (e.g.…”
Section: Physiological State Variablesmentioning
confidence: 99%
“…In a seasonal environment, it is important for animals to control the timing of activities. Mechanisms for this are discussed by Paul et al (2008) and Wikelski et al (2008).…”
Section: Introduction Adaptation To the Annual Cyclementioning
confidence: 99%